Revolution to Devolution : Reflections on Welsh Democracy - Morgan, Kenneth O. (University of Wales Press, 2014)
This is an integrated range of studies focusing on Wales by a long-established and internationally-recognised academic authority and member of the House of Lords on the advance of democracy and the evolving idea of national identity in modern Britain.